Analysis of Climate Change Adaptation Program Implementation on Urban Riverside Low Income Communities, Indonesia - Andie Arif Wicaksono; Atik Suprapti; Sunarti Sunarti (Journal of Architectural Design and Urbanism, 2022)
Climate change in urban areas has more aggravated focus as more and more humans are living near city centers. Climate change in the form of heavy rains with medium and high intensity makes floods often occur on the banks of urbanized rivers. This article aims to show the characteristics of slum riverside settlements within Yogyakarta city and the optimal quality improvement program for settlements in that place. Kampung Suranatan, Gemblakan Bawah, and Mrican-Giwangan located on the banks of the Winongo, Code, and Gajahwong rivers in the city of Yogyakarta are inhabited by low-income communities. This purposive sampling research was conducted using the snowballing method on eight informants to map the conditions, climate change adaptation program implementation as well as determine the most optimal program. The results showed that although they were often hit by floods, these three kampungs were able to survive because the communities in them were proactive in various environmental conservation movements, especially riverbanks. This proactiveness is the most important provision to become a climate-resilient kampungs.